Distance Learning and Emergency Remote Teaching: Concepts in Debate - Toledo, Stefani Moreira Aquino (2023)
This bibliographic research aims to discuss the similarities and differences between the concepts of Distance Education (DE), Emergency Remote Teaching (ERT) and other new denominations that emerged with the adoption of ERT in basic education schools during the pandemic. Thus, theoretical references were used about DE and ERT and about the terminology used to designate the ERT adopted in the state schools in Minas Gerais (MINAS GERAIS, 2020; TOLEDO, 2021). The results of the discussions pointed out convergences and divergences between DE and ERT. The mediation of the teaching and learning process by Digital Information and Communication Technologies (DICT) is similar in both cases, but official regulation as a teaching modality is recognized only in distance education. The ERT was adopted, in turn, as an interim strategy to minimize the consequences of the basic education school closures due to the conditions imposed by Covid-19 pandemic. Therefore, this bibliographic research presents complementary discussions to previous studies on both terminologies, DE and ERT, adding a discussion about the context of the state public schools of Minas Gerais. Finally, it is expected to contribute to the reflection and analysis of the influence of the concepts addressed here before practices adopted in the teaching network in question, in the most critical period of the Covid-19 pandemic.   Keywords: Distance education. Emergency remote teaching. Basic education. Pandemic.